Influence of the Modes of Laser Alloying on the Parameters of Wear Resistance of 12Kh17T Steel - Duryahina, Z. А.; Kuzin, Oleg A.; Kuzin, Mykola O.; Shcherbovs’kykh, N. V. (Springer, US, 2011)
EN: By using the approaches of contact mechanics, we analyze the influence of laser alloying with Nb, B, and Ni on the behavior of the parameters of wear resistance of 12Kh17Т steel. It is shown that, in the process of operation of the components in the case where the force load is much lower than the yield strength of steel, it is reasonable to perform laser alloying by using a CO2 -laser with a power of 800 W. At the same time, in the case where the load is equal to the yield strength, it is reasonable to apply a laser with a power of 6.5 kW which increases the contact strength of the subsurface layers.

UK: Використовуючи підходи контактної механіки, ми аналізуємо вплив лазерного легування з Nb, B і Ni на поведінці параметрів зносостійкості 12Kh17T сталі. Показано, що в процесі експлуатації компонентів в разі, коли навантаження сила набагато нижча, ніж межа плинності сталі, доцільно виконати лазерне легування за допомогою СО 2-лазера з потужністю 800 Вт. В той же час, у разі, коли навантаження дорівнює межі текучості, то розумно застосувати лазер з потужністю 6,5 кВт, яке збільшує міцність контакту підповерхневих шарів.

RU: Используя подходы контактной механики, мы анализируем влияние лазерного легирования с Nb, B и Ni на поведении параметров износостойкости 12Kh17T стали. Показано, что в процессе эксплуатации компонентов в случае, когда нагрузка силы гораздо ниже, чем предел текучести стали, целесообразно выполнить лазерное легирование с помощью СО 2-лазера с мощностью 800 Вт. В то же время, в случае, когда нагрузка равна пределу текучести, то разумно применить лазер с мощностью 6,5 кВт, которое увеличивает прочность контакта подповерхностных слоев.
Вплив режимів лазерного легування на параметри зносостійкості 12Kh17T стали
Влияние режимов лазерного легирования на параметры износостойкости 12Kh17T стали
M. Kuzin: ORCID 0000-0002-6032-4598
Keywords: wear resistance; contact strength; laser alloying; steel; зносостійкість; контактна міцність; лазерне легування; сталь; износостойкость; контактная прочность; лазерное легирование; КРС (ЛФ)